Mapping the Jural Border between Ireland and Northern Ireland - Oran Doyle (Review of Irish Studies in Europe, 2023)
Northern Ireland challenges a Westphalian account of the world in which sovereign states inhabit discrete geographic spaces. Its constitutional future is not determined by the central UK Government, its external border is porous for people and open for goods, some parts of EU law continue to apply. The paper shifts the focus from unitary and coherent sovereign spaces to multiple, varied and overlapping jural spaces, shedding light on some of the challenges that would be faced in the context of Irish unification. Even in a politically unified Irish state, managing the jural border between Ireland and Northern Ireland would remain a key task. The paper outlines a new account of law’s relationship to geographical space, before analysing the border between Ireland and Northern Ireland. The paper concludes by addressing some structural issues that would need to be addressed if Irish unification were to occur.